1983
DOI: 10.1093/jac/11.suppl_c.43
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of mezlocillin and carbenicillin on haemostasis in volunteers

Abstract: Mezlocillin and carbenicillin were administered intravenously to healthy male volunteers, for six days each, in a double-blind crossover study. Tests to detect abnormalities in haemostasis were performed before, during and after administration. Platelet aggregation studies indicated that both antibiotics interfered with platelet aggregation and secretion resulting in prolonged bleeding times. The effect was dose related and rapidly reversible after discontinuation of the antibiotics. It always occurred earlier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In agreement with results of a previous study (2), moxalactam was found to inhibit ADP-induced aggregation; the effects were typical of those reported for other P-lactam antibiotics in healthy volunteers (1,2,4,5,7,17). Specifi (2) and indeed for other ,B-lactam antibiotics (5,7,17).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with results of a previous study (2), moxalactam was found to inhibit ADP-induced aggregation; the effects were typical of those reported for other P-lactam antibiotics in healthy volunteers (1,2,4,5,7,17). Specifi (2) and indeed for other ,B-lactam antibiotics (5,7,17).…”
Section: Resultssupporting
confidence: 91%
“…Specifi (2) and indeed for other ,B-lactam antibiotics (5,7,17). It should be noted that reduced responsiveness to collagen is not inconsistent with the ANTIMICROB.…”
Section: Resultsmentioning
confidence: 91%
“…Their lower sodium content is an advantage in treating patients who are adversely affected by large sodium loads. Finally, mezlocillin (4,17) and possibly piperacillin (11) have less of a deleterious effect on platelet aggregation than do the a-carboxypenicillins and, therefore, may cause less bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…2). These penicillins have also demonstrated an ability to produce platelet dysfunction and clinical bleeding (Copeland et al 1983). …”
Section: Nomentioning
confidence: 99%